Tocilizumab for the fifth progression of cystic childhood craniopharyngioma—a case report - de Vos-Kerkhof, Evelien; Buis, Dennis R.; Lequin, Maarten H.; Bennebroek, Carlien A.; Aronica, Eleonora; Hulleman, Esther; Zwaveling-Soonawala, Nitash; van Santen, Hanneke M.; Schouten-van Meeteren, Antoinette Y. N. (Frontiers in Endocrinology, 2023)
We present the case of a 15-year-old girl, with a fifth cystic progression of an adamantinomatous craniopharyngioma after multiple surgeries and previous local radiotherapy. She had severe visual impairment, panhypopituitarism including diabetes insipidus and several components of hypothalamic damage, including morbid obesity and severe fatigue. To prevent further late effects hampering her quality of survival, she was treated biweekly with intravenous tocilizumab, an antiinterleukin-6 agent, which stabilized the cyst for a prolonged time. Based on the biology of adamantinomatous craniopharyngioma, this immune-modulating treatment seems promising for treatment of this cystic tumor in order to reduce surgery and delay or omit radiotherapy.